2017
DOI: 10.1111/vde.12500
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the correlation of serum IL‐31 with severity of dermatitis in an experimental model of canine atopic dermatitis using beagle dogs

Abstract: Background -IL-31 is a cytokine that is believed to play an important role in atopic dermatitis (AD). IL-31 levels positively correlate with disease severity in children with AD. Currently, there is no study that has investigated such a correlation in atopic dogs.Hypothesis/objective -The purpose of this study was to evaluate the correlation between IL-31 serum levels and severity of dermatitis. It was hypothesized that a positive correlation exists between severity of AD and circulating levels of IL-31.Animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 13 publications
(36 reference statements)
2
15
1
1
Order By: Relevance
“…A previous study reported that the production of IL‐17A in the peripheral blood mononuclear cells of dogs was associated with adverse food reaction (AFR) . It was suggested that the possible association of IL‐17 with concurrent bacterial infection was because IL‐17 was not correlated with clinical improvement but rather with the bacterial count . However, in our study, none of the dogs with AD was suffering from concurrent microbial infection.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…A previous study reported that the production of IL‐17A in the peripheral blood mononuclear cells of dogs was associated with adverse food reaction (AFR) . It was suggested that the possible association of IL‐17 with concurrent bacterial infection was because IL‐17 was not correlated with clinical improvement but rather with the bacterial count . However, in our study, none of the dogs with AD was suffering from concurrent microbial infection.…”
Section: Discussioncontrasting
confidence: 64%
“…Marked elevation in IL‐31 in pruritic versus nonpruritic human skin conditions and correlation of serum IL‐31 concentrations with the severity of disease in adult humans and children with AD has been documented . Similarly, a positive correlation between the severity of canine AD and circulating IL‐31 concentrations has been reported . The administration of canine IL‐31 to dogs resulted in a significant increase in pruritic behaviour .…”
Section: Discussionmentioning
confidence: 90%
“…These results suggest that the Th2 response is increased and the Th1 response is decreased in the isolated PBMCs from AD dogs. Particularly, IL-31 (a TH2 cytokine) has attracted a lot of attention in recent years for its role in pruritus and atopic inflammation, and recent studies demonstrated serum IL-31 levels positively correlate with disease severity in both children and dogs with AD [50, 51]. Although total serum IgE levels are elevated in the humans with AD [52, 53], the values are of no clinical relevance in the AD dogs in this study, which is in agreement with previous reports [34, 35].…”
Section: Discussionmentioning
confidence: 99%
“…Important role in atopic pruritus [167 ]. Its serum concentration correlates with the severity of active skin lesions [168 ]…”
Section: Canine Atopic Dermatitismentioning
confidence: 99%